2021
DOI: 10.3390/ph14070642
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the New Insulin-Resistant Zebrafish Model

Abstract: Insulin resistance, which occurs when insulin levels are sufficiently high over a prolonged period, causing the cells to fail to respond normally to the hormone. As a system for insulin resistance and diabetes drug development, insulin-resistant rodent models have been clearly established, but there is a limitation to high-throughput drug screening. Recently, zebrafish have been identified as an excellent system for drug discovery and identification of therapeutic targets, but studies on insulin resistance mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Quantitative PCR analysis was used in this study, showing the time point group designation as shown in the references from previous studies [ 25 , 27 ]. The study is important in terms of glucose dynamic study at different time points to validate that hyperinsulinemia induction can induce hyperglycemia and the transposition of insulin signaling genes ( pepck and akt ) affecting two genes involved in neurodegeneration ( zglut3 and claudin-5a ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Quantitative PCR analysis was used in this study, showing the time point group designation as shown in the references from previous studies [ 25 , 27 ]. The study is important in terms of glucose dynamic study at different time points to validate that hyperinsulinemia induction can induce hyperglycemia and the transposition of insulin signaling genes ( pepck and akt ) affecting two genes involved in neurodegeneration ( zglut3 and claudin-5a ).…”
Section: Resultsmentioning
confidence: 99%
“…Coinciding with the loss of insulin sensitivity, perturbation of glucose homeostasis was observed due to the downregulation of phosphoenolpyruvate carboxykinase ( pepck ) and the dephosphorylation of the Akt pathway upon microinjection of insulin (250 nM and 100 nM) into the caudal aorta at 4 days post fertilization (dpf) in larvae [ 25 ]. Similarly, Rocha et al, (2013) and Nam et al, (2021) studies indicate that glucose acts on the physiological changes in zebrafish larvae by glucose and insulin immersion, respectively [ 26 , 27 ]. Nam et al, (2021) focused on the characterization of insulin resistance in a T2DM model in MAPK signaling pathways encoded by the map2k6 -gene-activated inflammatory cytokines [ 27 ].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, incubating zebrafish with MG solutions can be a more straightforward way to establish diabetic model [24]. In addition, treating zebrafish embryos with high insulin concentration in a short-term (no more than 120 min) can lead to a hyperinsulinemia condition and a long-term (48 h) treatment causes insulin-resistant in zebrafish that mimics human type 2 DM [25]. Because obesity is usually a major factor for developing type 2 DM in humans, Zang et al [26] construct the obesity-induced zebrafish diabetic model via overfeeding.…”
Section: Zebrafish Dm Models: Advantages and Disadvantagesmentioning
confidence: 99%